Profiling plasma N-Acylethanolamine levels and their ratios as a biomarker of obesity and dysmetabolism - Flaminia Fanelli; Marco Mezzullo; Andrea Repaci; Ilaria Belluomo; Daniela Ibarra Gasparini; Guido Di Dalmazi; Marianna Mastroroberto; Valentina Vicennati; Alessandra Gambineri; Antonio Maria Morselli-Labate; Renato Pasquali; Uberto Pagotto (Molecular Metabolism, 2018)
Objective: N-acylethanolamines play different roles in energy balance; anandamide (AEA) stimulates energy intake and storage, N-palmitoylethanolamide (PEA) counters inflammation, and N-oleoylethanolamide (OEA) mediates anorectic signals and lipid oxidation. Inconsistencies in the association of plasma N-acylethanolamines with human obesity and cardiometabolic risk have emerged among previous studies, possibly caused by heterogeneous cohorts and designs, and by unstandardized N-acylethanolamine measurements. We aimed to characterize changes in the plasma profile, including N-acylethanolamine levels and ratios associated with obesity, menopause in women, and ageing in men, and to define the significance of such a profile as a biomarker for metabolic imbalance. Methods: Adult, drug-free women (n = 103 premenopausal and n = 81 menopausal) and men (n = 144) were stratified according to the body mass index (BMI) into normal weight (NW; BMI: 18.5–24.9 kg/m2), overweight (OW; BMI: 25.0–29.9 kg/m2), and obese (OB; BMI ≥30.0 kg/m2). Anthropometric and metabolic parameters were determined. Validated blood processing and analytical procedures for N-acylethanolamine measurements were used. We investigated the effect of BMI and menopause in women, and BMI and age in men, as well as the BMI-independent influence of metabolic parameters on the N-acylethanolamine profile. Results: BMI and waist circumference directly associated with AEA in women and men, and with PEA in premenopausal women and in men, while BMI directly associated with OEA in premenopausal women and in men. BMI, in both genders, and waist circumference, in women only, inversely associated with PEA/AEA and OEA/AEA. Menopause increased N-acylethanolamine levels, whereas ageing resulted in increasing OEA relative abundance in men. AEA and OEA abundances in premenopausal, and PEA and OEA abundances in lean menopausal women, were directly associated with hypertension. Conversely, PEA and OEA abundances lowered with hypertension in elderly men. Insulin resistance was associated with changes in N-acylethanolamine ratios specific for premenopausal (reduced PEA/AEA and OEA/AEA), menopausal (reduced OEA/AEA) women and men (reduced OEA/AEA and OEA/PEA). PEA and OEA levels increased with total cholesterol, and OEA abundance specifically increased with HDL-cholesterol. Elevated triglyceride levels were associated with increased N-acylethanolamine levels only in menopausal women. Conclusions: Obesity-related N-acylethanolamine hypertone is characterized by imbalanced N-acylethanolamine ratios. The profile given by a combination of N-acylethanolamine absolute levels and ratios enables imbalances to be identified in relationship with different metabolic parameters, with specific relevance according to gender, menopause and age, representing a useful means for monitoring metabolic health. Finally, N-acylethanolamine system appears a promising target for intervention strategies. Keywords: Anandamide, N-palmitoylethanolamide, N-oleoylethanolamide, Endocannabinoid system, Obesity, Dysmetabolism